FARM WOMEN PARTICIPATORY ON-FARM TRIAL (OFT) ON PREVENTION AND CONTROL OF MASTITIS IN DAIRY CATTLE - P. Mathialagan; G. Kumarasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Two hundred women self help group members having dairy cattle were purposively selected from ten different villages in Namakkal district for this study. A Multi-disciplinary team of scientists conducted the on-farm trial and institutional training programme for the beneficiaries on different selected technologies and the demonstrations on cleaning of dairy cattle, disinfection and sanitation of shed, milking methods, cleaning of udder, wiping of udder, strip cup test-mastitis detection and teat dipping were conducted. Inputs like mastitis detection Kit (Sodium lauryl sulphate reagent, strip cups), post teat dip container, povidone iodine, plastic hand sprayer, potassium permanganate, plastic bottles, test tubes for milk sample collection and reading materials were distributed to all the beneficiaries. Regular follow up was made to guide the farm women for conducting the on-farm trial (OFT). The beneficiaries reported that there was reduction in the occurrence of mastitis both in cows and buffaloes from 9.5 per cent to 1.5 per cent and 1.4 per cent to nil, respectively after imparting knowledge and skills on the mastitis detection and control techniques. The keeping quality of milk was also found to be improved through increase in Methylene blue dye reduction time of 25 minutes to one hour for cow milk and from 15 minutes to 45 minutes for buffalo milk. There was significant reduction in the somatic cell count of milk of cows and buffaloes by the adoption of the technologies.